Analysis of the Influence of Customer Experience and Customer Value on Customer Loyalty with Customer Satisfaction as a Mediating Variable in Umrah Travel Agencies in Indonesia - Xaviera Amalia Putri; Ali; Anna Widiastuti (International Journal of Economics, Business and Innovation Research, 2026)
This study aims to analyze the factors that influence pilgrim loyalty in the Umrah travel agency industry in Indonesia, with a focus on the role of Customer Experience (CE), Customer Value (CV), and Customer Satisfaction (CS). Using a quantitative approach with the Partial Least Squares (PLS)-based Structural Equation Modeling (SEM) method, data was collected from pilgrims who had used Umrah travel services. The results showed that customer experience and customer value had a positive and significant effect on customer satisfaction. Furthermore, customer satisfaction was found to play a significant mediating role in linking customer experience and value to loyalty. These findings emphasize that to maintain loyalty amid intense competition in the travel industry, companies must focus on creating satisfaction through memorable worship experiences and superior service value. Keywords: Customer Experience, Customer Value, Customer Satisfaction, Customer Loyalty, Umrah Travel Industry, PLS-SEM.